2019
DOI: 10.5713/ajas.18.0347
|View full text |Cite
|
Sign up to set email alerts
|

The alternative approach of low temperature-long time cooking on bovine semitendinosus meat quality

Abstract: The innovative sous vide treatment with double thermal effect appears an attractive cooking method as compared to common sous vide and traditional cooking method, as it has a potential for improving tenderness values of cooked beef semitendinosus muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
8
16
0
Order By: Relevance
“…Murphy et al [42] reported that the denaturation of myosin and actin at higher temperatures caused structural changes and changes in porosity of the chicken breast patties which can directly affect the moisture content. This result is in accordance with those obtained for chicken and beef [28,43].…”
Section: Moisture Content Cooking Loss and Phsupporting
confidence: 93%
“…Murphy et al [42] reported that the denaturation of myosin and actin at higher temperatures caused structural changes and changes in porosity of the chicken breast patties which can directly affect the moisture content. This result is in accordance with those obtained for chicken and beef [28,43].…”
Section: Moisture Content Cooking Loss and Phsupporting
confidence: 93%
“…We expect by increasing the temperature with the prolonged cooking of sous vide treated beef could increase soluble collagen but instead, it shows lower CS values at 70°C. Similarly, our previous finding in the application of sous vide treatment on bovine semitendinosus muscles at 65°C for 3 h and at 45°C–65°C for 6 h had lower soluble collagen than non-sous vide meat cooked at 75°C for 30 min ( Ismail et al, 2019 ). From those findings, one can conclude that prolonged cooking time in sous vide could reduce soluble collagen by the CL and this observation also has supported by Weston et al (2002) .…”
Section: Resultssupporting
confidence: 77%
“…The lower toughness of combine temperature-time in 2T2T treatment might be attributed by double thermal effect. In our previous study, beef semitendinosus treated with low temperature-long time at 45°C showed the lowest SF values (Ismail et al, 2019). According to Myhrvold et al (2011) and Lawrie (1998), the tenderness of cooked meat can be achieved at cooking temperature 45°C and 49°C even cooked for 4 h. It is noteworthy that at a low temperature some of the key enzymes such as calpains, cathepsins, and collagenase play an important role to the degradation of the myofibrillar components and may contribute to reducing actomyosin toughness.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In the same line, Lorenzo et al [ 34 ] evidenced this trend, because they concluded that grilling in foal meat also generated less hardness slices compared to other treatments (roasted, fried and microwaved). Besides, according to Ismail et al [ 49 ] the Pearson correlation demonstrated that shear force was positively related to cooking loss (r = 0.301; P > 0.05; and r = 0.562; P < 0.01 for CH and CF, respectively). However, there were only significant ( P < 0.01) differences in CF samples.…”
Section: Resultsmentioning
confidence: 97%